Źródła etyki doradztwa w filozofii starożytnej - Mrówka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2011)
Advising is an important area of human activity, it helps to clarify own experiences and thoughts, increases self-awareness and competence, leads to well grounded decisions and choices. In modern times advising gained even more importance as it has successfully became a part of a business world. This very practical aspect of advising significantly influences development of technology, management methods and organization of human work, while at the same time it may lead to problems and risks of economical, political or ecological nature. Hence advising should be supported by philosophical consideration and ethical assessment – this is even more so, as advising in it’s theoretical, methodological and ethical foundations is well grounded in philosophy. Main perspectives of reflection on advising are driven by traditional philosophical questions and disputes. Historical research shows that many virtues are of stable properties that last across ages. Thus, drawing on experience of philosophers-advisors from Sophists, Socrates, Plato, Aristotle and Seneca we see that practical philosophy can give support in solving different problems of business advisory and can help in drawing professional code rules of advisor.